Failure points in the PKI architecture / Точки отказа в PKI архитектуре / Tačke otkaza u PKI arhitekturi - Radomir I. Prodanović; Ivan B. Vulić (Vojnotehnički Glasnik, 2017)
Over the last 20 years, the PKI architecture has found its vast application, especially in the fields which require the establishment of a security infrastructure. Given that the purpose of this architecture is to be used for achieving higher security standards, its smooth operation has to be one of the main requirements for its implementation. Its complexity is mirrored in the numerous implementations that the PKI has had so far. For all the reasons mentioned above, it is of great importance to consider potential failure points of such a structure. Due to the complexity of these structures, this paper will present only a basic review of such stress points, without providing details on specific applications and types of implementations. The significance of failure points will be explained by examining the common features of the PKI architectures and the occurrence of failure points in these structures, and where possible, an overview of suggestions for preventing such failures will be provided. / За последних двадцать лет, архитектура PKI стала широко применяться, особенно в областях, требующих создания инфраструктуры безопасности. Учитывая, что цель создания такой архитектуры заключается в обеспечении безопасности систем, главными задачами при внедрении архитектуры PKI являются бесперебойная работа и взаимодействие с другими компонентами комплектной структуры. Из вышеизложенного следует, что прогноз потенциальных точек отказа представляет собой исключительно важный фактор. В связи с ограничением объема статьи, и так как речь идет о значительно сложных инфраструктурах, в данной работе представлен лишь общий обзор главных потенциальных точек отказа, без подробного объяснения характеристик по каждому отдельному виду внедрения архитектуры. В статье исследуются общие характеристики PKI архитектур, на основании которых трактуется значение возможных отказов и предлагаются мероприятия по предупреждению и преодолению данного рода проблемы. / Tokom poslednjih 20 godina PKI arhitektura našla je široku primenu, posebno u oblastima koje su zahtevale uspostavljanje sigurnosne infrastrukture. S obzirom na to da se koristi radi sigurnosti jasno je da je njen nesmetan rad jedan od osnovnix zahteva koji se postavlja pri njenoj implementaciji, a već samim uvidom u brojne tipove arhitektura i različite implementacije uviđa se njena kompleksnost. Zbog toga je razmatranje potencijalnih tačaka otkaza od velike važnosti. Kako se radi o vrlo složenim infrastrukturama, ovaj rad daće samo osnovni pregled tačaka koje mogu biti tačke otkaza, bez detalja koji su karakteristični za pojedine primene i tipove implementacija.Tražiće se zajedničke karakteristike PKI arhitektura i na njima objašnjavati značaj otkaza koji se mogu desiti, a tamo gde je moguće biće navedeni i predlozi za njihovo prevazilaženje.